2011
DOI: 10.1093/jac/dkq537
|View full text |Cite
|
Sign up to set email alerts
|

Biological activity of three novel complexes with the ligand 5-methyl-1,2,4-triazolo[1,5-a]pyrimidin-7(4H)-one against Leishmania spp.

Abstract: Cellular proliferation, metabolic and ultrastructural studies showed that the compounds 2>1>3 were highly active against L. infantum and L. braziliensis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
13
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(14 citation statements)
references
References 14 publications
1
13
0
Order By: Relevance
“…T. cruzi excretes acetate and succinate as majority metabolites and, in a lower proportion, L-alanine. This data agree well with other authors [35]. We carried out the identification and evaluation of the inhibiting effect caused by the compounds by using 1 H NMR, whose spectra showed that only compound 2 leads to an alteration on the metabolites excreted by T. cruzi.…”
Section: Metabolite Excretion Effectsupporting
confidence: 92%
“…T. cruzi excretes acetate and succinate as majority metabolites and, in a lower proportion, L-alanine. This data agree well with other authors [35]. We carried out the identification and evaluation of the inhibiting effect caused by the compounds by using 1 H NMR, whose spectra showed that only compound 2 leads to an alteration on the metabolites excreted by T. cruzi.…”
Section: Metabolite Excretion Effectsupporting
confidence: 92%
“…Compared with purines, the fused-ring system of these ligands differs only in the presence of a pyrimidine nitrogen atom in a bridgehead position and the disappearance of the acidic H-proton of the five-membered ring [6,7]. Furthermore, these bicyclic heterocycles have been subjected to chemical and biological tests due to their pharmacological properties, including anticancer [8,9], antibacterial [10], antiviral [11], anti-inflammatory [12,13], fungicidal [14], antiparasitic [15][16][17][18][19] and leishmanicidal properties [20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, recent findings on compounds of metal ions (Co(II), Cu(II), Ni(II)) with closely related ligands, have proven to be effective antiparasital agents against Trypanosoma cruzi [14] and to be endowed with antiproliferative in vitro activity against Leishmania spp. [15]; the biological activity on these specimen is still in progress [16]. Staphylococci can induce a wide spectrum of infectious diseases associated with remarkable morbidity and mortality [17].…”
mentioning
confidence: 99%